2022
DOI: 10.3390/jcm11041137
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Serum Creatine Phosphokinase Levels and Acute Kidney Injury among ST-Segment Elevation Myocardial Infarction Patients

Abstract: Background: Among patients with rhabdomyolysis, the leakage of intracellular skeletal muscle content such as creatine phosphokinase (CPK) into the bloodstream has been associated with an increased risk of acute kidney injury (AKI). We evaluated the possible relationship between serum CPK levels and AKI occurrence among patients with myocyte injury secondary to ST-elevation myocardial infarction (STEMI). Methods: We retrospectively included 2794 patients with STEMI. Patients were stratified according to peak se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Moreover, myoglobin is reabsorbed by the proximal tubule cells and promotes oxidative stress, resulting in cortical acute tubular necrosis which is the hallmark of renal pathology in this model [ 11 ]. Thus, since higher CPK levels were associated with acute renal failure and the need for renal replacement therapy in patients [ 51 ], our findings suggest that therapeutic targeting of GSK3β with lithium treatment initially ameliorated rhabdomyolysis-induced AKI probably due to a decrease in CPK plasma levels.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, myoglobin is reabsorbed by the proximal tubule cells and promotes oxidative stress, resulting in cortical acute tubular necrosis which is the hallmark of renal pathology in this model [ 11 ]. Thus, since higher CPK levels were associated with acute renal failure and the need for renal replacement therapy in patients [ 51 ], our findings suggest that therapeutic targeting of GSK3β with lithium treatment initially ameliorated rhabdomyolysis-induced AKI probably due to a decrease in CPK plasma levels.…”
Section: Discussionmentioning
confidence: 89%
“…Hepatic steatosis also increases oxidative stress through significant lipid metabolism [ 45 ]. Serum total CPK and proteinuria are predictive markers of heart and kidney damage [ 37 , 46 ]. Significantly elevated serum levels of CPK and LDL-cholesterol, as well as the presence of albuminuria, are often associated with cardiovascular events and nephrotic syndrome [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum total CPK and proteinuria are predictive markers of heart and kidney damage [ 37 , 46 ]. Significantly elevated serum levels of CPK and LDL-cholesterol, as well as the presence of albuminuria, are often associated with cardiovascular events and nephrotic syndrome [ 46 , 47 ]. Administration of P. erinaceus extract and glibenclamide for three weeks caused a significant decrease (p < 0.001) in transaminases (ALT, AST), triglycerides, LDL-cholesterol and CKP in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rhabdomyolysis may further contribute to the occurrence of AKI. Zahler et al [41] recently demonstrated that increased levels of creatine phosphokinase were associated with the occurrence of AKI in 2,794 patients with STEMI. In line with this, hemolysis was shown to further contribute to AKI [42].…”
Section: Acute Kidney Injury In Cardiogenic Shockmentioning
confidence: 99%